Filling black holes – using business process analysis in criminal intelligence. Issue 3 (3rd July 2017) - Murray, Kenneth
Abstract : Purpose: The purpose of this paper is to highlight the importance of improving financial intelligence capture in understanding organized crime and the funding of terrorism. Design/methodology/approach: The paper presents an analytical review of the core business processes used to harvest the revenues from illegal drug trafficking. Furthermore, assessment of the extent to which modern, organised crime – and the dynamics of the relationships between the relevant collaborating parties – can be more accurately defined in terms of these processes. Findings: Understanding distinctive capabilities of criminal funding processes as well as their participants offers an approach to filling intelligence black holes which continue to afflict efforts to tackle organised crime and terrorism. Originality/value: This paper establishes a framework for understanding and countering threat through application of competitive strategy analysis.